Characterization of a Polymorphism in the Stimulatory Region of the TNF Gene in Type 2 Diabetic Patients in Iraq (Journal of Pharmaceutical Negative Results, 2022)
The current study aims to analyze the distribution of the TNF-α gene and TNF-β polymorphism (-308G/A) in type 2 diabetes mellitus (T2DM) patients. According to world health organization the prevalence of diabetes is rising exponentially. Tumor necrosis factor alpha and beta are members of the tumor necrosis factor (TNF) super-family considered as pro inflammatory cytokine which play major role in DM pathogenesis. single nucleotide polymorphism reported to have associated with type 2 DM. Frequency of TNF-a G308A polymorphism was determine in different ethnic groups and was found variable highly. Few studies recorded appositive association between DM and TNF-α polymorphism; including meta-analysis failed to find such association. Our finding revealed that the TNF-α gene polymorphism (-308G/A) had 38 (12.50%) of G/G genotype, 44 (45.83%) of G/A genotype and 40 (41.67%) A/A genotype showed in this population. This preliminary result indicated that G/A genotype was a common in the TNF-α gene polymorphism (-308G/A) in T2DM patients while healthy control group does not exhibit AA and GA genotype.